Latin American States’ Multilateral Diplomacy - S. A. Krylov (Vestnik MGIMO-Universiteta, 2009)
This article reveals the mechanism of functioning of the multilateral diplomacy of the Latin American and Caribbean States on the subregional, regional level as well as in the biregional format and analizes the perspectives of the integrational processes in the Western hemisphere in the context of formation of a new world structure of the XXI century.